Workflow Automation in Digital Medication Reminder Systems to Enhance Patient Adherence - Salsabila Intania Bestari; Syafrijon; Randi Proska Sandra; Ahmaddul Hadi (Universitas Negeri Padang, 2026)
Pharmacotherapy is a form of treatment that utilizes pharmaceutical products as a medium for healing. The effectiveness of this therapy largely depends on patient adherence and consistency in taking medication as prescribed by physicians. Unfortunately, in practice, many cases of non-adherence occur, leading to medication errors and reduced treatment outcomes. This study proposes a solution by employing workflow automation technology combined with several API integrations, such as WhatsApp API and Google Calendar API, to provide a broader and more accessible user experience. The proposed system is a web-based platform connected to n8n, a workflow automation tool that supports integration with third-party applications like WhatsApp and Google Calendar. First-party users, such as doctors and hospital operators, can input patients’ medication schedules into the system. The system then sends reminders and confirmations to second-party users (patients) via WhatsApp, while also synchronizing schedules through Google Calendar. WhatsApp was selected due to its popularity and accessibility in Indonesia, while Google Calendar was chosen as one of the most widely used calendar applications worldwide. This research is expected to contribute to pharmacotherapy support by providing a simple yet practical technological approach to improve medication adherence.